Pengaruh Lingkungan Fisik, Lingkungan Non Fisik, dan Keterampilan terhadap Produktivitas Kerja Karyawan CV Semeru Jaya Teknik Palembang - Dedi Hartawan Hartawan; LEMIYANA LEMIYANA (Jurnal Keuangan dan Bisnis, 2019)
The physical work environment has a positive and significant effect on employee work productivity. This can be seen from the calculation results for the first hypothesis Y = 24,813 + 0,244X1. A value of 0.244 indicates that the physical work environment has a positive influence on employee work productivity. The condition of the work environment owned by a company will affect the success or failure of a job that is shown from the ability of employees to complete the work to achieve company goals. The non-physical work environment calculation for the second hypothesis is Y = 24,813 - 0,037 X2. A b2 value of -0.037 indicates that the non-physical work environment has a negative influence on employee work productivity. It was concluded that the non-physical work environment is felt to be able to support employees in completing work, so employees will feel satisfied at work, and vice versa. The multiple linear regression equation obtained from the calculations for the third hypothesis is Y = 24,813 + 0,190 X3. A b3 value of 0.190 indicates that the non-physical work environment has a negative influence on employee work productivity. It was concluded that the non-physical work environment is felt to be able to support employees in completing work, so employees will feel satisfied at work, and vice versa.